Social and real-property management during infrastructure construction for public transportation systems in five Colombian cities (analytical research) (REVISTA NODO, 2011)
As an introduction, the article presents a general overview of five Colombian cities demographical growth and their current urban transportation, including, Cartagena, Bucaramanga, Barranquilla, Medellin and Pereira. Then, it analyzes thoroughly social and real-property management during infrastructure construction for each of their new public transportation systems (SITM, in Spanish), emphasizing on their objectives, budgets, strategies, methodologies, data-analysis approaches, object groups involved, real state purchase and development stages. Finally, it revises project results and its indicators to conclude that the new paradigm for infrastructure construction is the environmental and social multidisciplinary intervention where works are taking place, since it allows for more comprehensive readings and more suitable answers to communities’ technical, juridical and social true-facts during real-property acquisition and social management overall
Keywords: Urban mobility; social urbanism; massive transportation